Macroeconomic Policies and Poverty Reduction : Stylized Facts and an Overview of Research - Cashin, Paul (IMF Working Papers; Working Paper, 2001)
This paper provides a brief and selective overview of research on the links between macroeconomic policies and poverty reduction. Using the Human Development Index as a measure of well-being, the progress made by 100 countries during 1975-98 is presented, and its association with macroeconomic factors is explored. Several potential avenues for future research are also outlined.